Characterization of the cellular transport mechanisms for the anti‐cachexia candidate compound TCMCB07. Issue 6 (29th July 2020) - Hu, Yongjun; Gruber, Kenneth A.; Smith, David E.
Abstract: Background: Cachexia is a debilitating, life‐threatening condition whose pathology includes reduced food intake accompanied by hypermetabolism, leading to a catabolic state. The hypothalamic melanocortin system is a critical regulator of metabolic rate with effects being mediated through the melanocortin‐4 receptor (MC4R). MC4R activation is also critical to the initiation and maintenance of cachexia. A major problem in the design of anti‐cachexia drugs has been the need to cross the blood–brain barrier to access the metabolic rate‐controlling centres in the hypothalamus. The overwhelming majority of anti‐cachexia drugs are only effective when administered intracerebroventricularly. TCMCB07 is a cyclic nonapeptide peptide MC4R antagonist with parenteral anti‐cachexia activity in both small and large animal models. This suggests it can cross the blood–brain barrier. The aim of this study was to examine potential transport mechanisms of TCMCB07 furthering its preclinical development for subsequent studies in humans. Methods: In vitro studies were performed in transporter‐transfected cells to study whether or not TCMCB07 was an inhibitor as well as substrate for OATP1A2, OATP1B1, OATP1B3, OATP2B1, OCT2, OAT1, OAT3, MATE1, MATE2‐K, P‐gp (MDR1), and BCRP. In vivo mass balance studies were also performed in mice to evaluate the absorption and disposition of TCMCB07 after oral and intravenous bolus administrations. Results: TCMCB07 inhibited the uptake of prototypical substrates in cells transfected with OATP1A2 (IC50 24.0 μM), OATP1B1 (IC50 6.8 μM), OATP1B3 (IC50 307 μM), OATP2B1 (IC50 524 μM), OCT2 (IC50 1, 169 μM), MATE1 (IC50 8.7 μM), and MATE2‐K (IC50 20.7 μM) but not in cells transfected with OAT1 and OAT3. TCMCB07 did not affect the P‐gp (MDR1)‐mediated and BCRP‐mediated permeability of prototypical substrates in transfected cells. Importantly, direct evidence was shown for the uptake of TCMCB07 in OATP1A2‐transfected cells (i.e. V max 236 pmol/mg, K m 58.4 μM, and K d 0.39 μL/mg), demonstrating that the nonapeptide was a substrate for this transporter. Mass balance studies demonstrated that 24.2% of TCMCB07 was absorbed orally in vivo ( P  = 0.0033) and excreted primarily in the bile after both oral and intravenous administrations. Conclusions: OATP1A2 is the transporter responsible for the oral absorption of TCMCB07 in the intestine and for its pharmacologic response in the brain.